The Therapeutic Potential of Apigenin - Salehi, Bahare; Venditti, Alessandro; Sharifi-Rad, Mehdi; Kręgiel, Dorota; Sharifi-Rad, Javad; Durazzo, Alessandra; Lucarini, Massimo; Santini, Antonello; Souto, Eliana B.; Novellino, Ettore; Antolak, Hubert; Azzini, Elena; et al. (International journal of molecular sciences, 2019)
Several plant bioactive compounds have exhibited functional activities that suggest they could play a remarkable role in preventing a wide range of chronic diseases. The largest group of naturally-occurring polyphenols are the flavonoids, including apigenin. The present work is an updated overview of apigenin, focusing on its health-promoting effects/therapeutic functions and, in particular, results of in vivo research. In addition to an introduction to its chemistry, nutraceutical features have also been described. The main key findings from in vivo research, including animal models and human studies, are summarized. The beneficial indications are reported and discussed in detail, including effects in diabetes, amnesia and Alzheimer’s disease, depression and insomnia, cancer, etc. Finally, data on flavonoids from the main public databases are gathered to highlight the apigenin’s key role in dietary assessment and in the evaluation of a formulated diet, to determine exposure and to investigate its health effects in vivo.